KITAB ‘BURDAH’ KARYA SASTRA LISAN ARAB DALAM PERSPEKTIF MASYARAKAT MUSLIM DI MANADO SULAWESI UTARA - Bachmid, Gayda (Universitas Sam Ratulangi, 2019)
This article reveals the role of Burdah as an Arabic literary book that has become a regular practice of the Moslem community in Manado. The researcher tries to find out the social and cultural aspects through the Arabic text pertaining to concrete condition where the content of the book is practiced and this serves as the key to comprehend the users’ view and thinking pattern. The problems paralleled to the research objective is identifying and analyzing the social, spiritual and metaphysical reflection. The research findings indicate socially, there is a unitary perception in which the user community is called to set up an organization to learn about the book. The projected spiritual transformation of the book as a prophecy work toward a future hope makes it a routine regular practice at wedding ceremony, housewarming, and children under five thanksgiving. Metaphysical transformation is held as a miracle so that this regular practice can cure various diseases. This belief rooted in the user community perception has become a daily routine custom even though the Arabic language read is not understood. Key words: Burdah, spiritual, cultural and metaphysical transformation.